2014
DOI: 10.1021/jp5071538
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Flow through a 1 mm2 Cross-Section Pore Placed in an Ion-Exchange Membrane

Abstract: In recent years, the control of ionic currents has come to be recognized as one of the most important issues related to the efficient transport of single molecules and microparticles in aqueous solutions. However, the complicated liquid flows that are usually induced by applying electric potentials have made it difficult to address a number of unsolved problems in this area. In particular, the nonequilibrium phenomena that occur in electrically non-neutral fields must be more thoroughly understood. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
(67 reference statements)
2
18
0
Order By: Relevance
“…Due to the concentration of the electric lines of force in a narrow channel, an almost uniform electric field is formed in the test section, which is suitable for the www.nature.com/scientificreports www.nature.com/scientificreports/ measurement of the electrical conductivity of electrolyte solutions. Using this method, it is expected that ion concentration fields as well as electric potentials at specific environments, such as interfaces at different size channel connections and near surfaces of ion-exchange membranes where enrichment and depletion occur under ionic current conditions [39][40][41] , are clarified. We will tackle such a challenging topic in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the concentration of the electric lines of force in a narrow channel, an almost uniform electric field is formed in the test section, which is suitable for the www.nature.com/scientificreports www.nature.com/scientificreports/ measurement of the electrical conductivity of electrolyte solutions. Using this method, it is expected that ion concentration fields as well as electric potentials at specific environments, such as interfaces at different size channel connections and near surfaces of ion-exchange membranes where enrichment and depletion occur under ionic current conditions [39][40][41] , are clarified. We will tackle such a challenging topic in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…The transport regime of microparticles is modified by the ion‐drag flow field. Here, we propose a novel method to generate the ion‐drag EHD flows [22, 23] in aqueous solution drastically decreasing the application voltage, where the external voltage does not exceed 2.0 V to avoid accelerating the electrolysis of water. We succeeded to dramatically reduce the applied voltage by preparing electrically polarised solutions.…”
Section: Introductionmentioning
confidence: 99%
“…They theoretically and experimentally investigated induced-charge electroosmosis and induced-charge electrophoresis of asymmetric metallic particles exposed to DC and AC electric fields. In previous studies, we also discussed charge induction effects that drove electrohydrodynamic flows of liquids. , The present study provides experimental results that suggested some possibilities of ionic current and flow characteristics induced by Au NPs at the nanoscale, and further details will be clarified in the future.…”
Section: Resultsmentioning
confidence: 63%
“…In previous studies, we also discussed charge induction effects that drove electrohydrodynamic flows of liquids. 57,58 The present study provides experimental results that suggested some possibilities of ionic current and flow characteristics induced by Au NPs at the nanoscale, and further details will be clarified in the future.…”
Section: ■ Results and Discussionmentioning
confidence: 73%